Advance care planning for subjects with early dementia – a pilot study. Issue 2 (1st June 2012) - Binte Ali, N; Chan, M; Anthony, P; Lim, WS; Chong, MS
Abstract : Lack of research in our multi-racial society, where different cultures have disparate beliefs with regards to death and dying, prompted us to conduct a pre-implementation feasibility study for the role of ACP on 9 patient-caregiver dyads from a memory clinic in Singapore. Subjects were recruited if they had mild dementia (global Clinical Dementia Rating of 0.5-1), no significant mood disorders or behavioural problems, and had an identified caregiver. Patients and their caregivers were surveyed individually for their understanding of ACP, and experience of communicating their end-of-life treatment preferences to their loved ones, before and after ACP counselling conducted by a trained ACP facilitator. Prior to ACP counselling, only 22% patients and 55% caregivers had heard of ACP. While 77% of patients rated their health status as good and 77% had thought of their healthcare proxy, only 22% made future care plans. After ACP counselling, 75% patients are keen for further ACP discussions and none admitted to barriers to communication compared to 62.5% caregivers who acknowledge barriers to communication. The percentage of patients who wished to receive therapy decreased as the likelihood of an adverse outcome (especially cognitive) increased. There is a disparity in the attitudes of patients and caregivers towards ACP where patients are more willing to discuss it compared to caregivers. Our study highlights the need for further education and dissemination of information on ACP among subjects with early dementia and their caregivers. We are intending to incorporate ACP and disseminate information on ACP in future dementia workshops.